Fabrication and characterisation of chitosan/poly vinyl alcohol nanofibres via electrospinning. (8th December 2014) - Talebian, S.; Afifi, A. M.; Khanlou, H. M.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, chitosan nanofibres were fabricated using electrospinning process. Initially, chitosan powders were further deacetylated with sodium hydroxide to deprotonate the polymer chains and decrease the molecular weight. Subsequently, the treated chitosan (5 wt-% in 90:10 acetic acid/water ratio) were mixed with poly vinyl alcohol (8 wt-% in water) at different ratios in order to facilitate the electrospinning through cross-links formation. Field-emission scanning electron microscopic images showed that 60:40 (chitosan/poly vinyl alcohol) ratio was the threshold for formation of beads (chitosan/poly vinyl alcohol >50:50 contains imperfections) and that increasing chitosan/poly vinyl alcohol ratio from 20:80 to 60:40 decreased the average diameter of fibres from 80 to 40 nm. Fourier transform infrared spectra proved the formation of chitosan/poly vinyl alcohol cross-linked nanofibres.